An Analysis Tourist’s Perceptions Toward Tourism Development: Secondary Tourist Attraction Study - Machmury, Andri (Universitas Sebelas Maret, 2024)
The findings of this study highlight that Dante Pine's success as a tourist destination largely depends on its natural attractions, such as the scenic mountain views and the outdoor ambiance. However, several operational improvements are needed to enhance the overall visitor experience. First, addressing the inadequate parking facilities and improving access to the site would significantly enhance visitor convenience, especially during peak times. Second, improving service speed and food quality, along with offering a wider range of food and beverage options, is essential to meet the expectations of growing tourist numbers. Third, strengthening safety measures on slippery pathways and enhancing family-friendly amenities, such as providing clean water and safe play areas for children, would address concerns raised by visitors. Lastly, diversifying attractions by revitalizing adventure activities like the flying fox or introducing new, engaging experiences could attract a broader audience. Future research could focus on understanding the impact of these operational improvements on visitor satisfaction and retention, with a particular focus on how to balance environmental sustainability with infrastructure development.